Study of Determining Factors for the Adoption of Sustainable Agribusiness Practices among Organic and Inorganic Coffee Farmers in Kayumas Village, Situbondo Regency - Fitriyaningsih, Fitriyaningsih; Muhlis, Abdullah; Hayati, Zainiatul (P3M Politeknik Negeri Jember, 2025)
The coffee plantation sector holds a strategic role in Indonesia’s economy, contributing to income, raw materials, and foreign exchange. In 2022, Indonesia had 1.29 million hectares of coffee plantations producing 794.8 thousand tons. East Java, particularly Kayumas Village in Situbondo with 1,500 hectares of land—partly certified organic—is a key production center. Growing environmental awareness has encouraged organic coffee cultivation, yet adoption of sustainable practices remains uneven as many farmers still apply inorganic systems. This study aims to identify the key factors influencing the adoption of sustainable agribusiness practices among organic and non-organic coffee farmers. Descriptive and analytical methods were used to systematically describe and analyze the relationship between variables using Binary Logistic Regression. The research location was purposively determined in Kayumas Village, Arjasa District. Respondents were purposively selected from two groups of organic and inorganic coffee farmers, using a quota sampling technique. The results show that, overall, the factors of land area, experience, business scale, partnerships, market access, and credit access influence coffee farmers' decisions to adopt sustainable agribusiness practices based on organic systems. However, in part, the variables of land area, experience, and medium and large business scale proved to have a significant effect. These findings confirm that farmers' resource and business capacity factors are the main determinants in the implementation of organic coffee farming systems.